Accuracy of Core Needle Biopsy Versus Fine Needle Aspiration Cytology for Diagnosing Salivary Gland Tumors - In Hye Song; Joon Seon Song; Chang Ohk Sung; Jong-Lyel Roh; Seung-Ho Choi; Soon Yuhl Nam; Sang Yoon Kim; Jeong Hyun Lee; Jung Hwan Baek; Kyung-Ja Cho (Korean Society of Pathologists & the Korean Society for Cytopathology, 2015)
Background: Core needle biopsy is a relatively new technique used to diagnose salivary gland lesions, and its role in comparison with fine needle aspiration cytology needs to be refined. Methods: We compared the results of 228 ultrasound-guided core needle biopsy and 371 fine needle aspiration procedures performed on major salivary gland tumors with their postoperative histological diagnoses. Results: Core needle biopsy resulted in significantly higher sensitivity and more accurate tumor subtyping, especially for malignant tumors, than fine needle aspiration. No patient developed major complications after core needle biopsy. Conclusions: We recommend ultrasoundguided core needle biopsy as the primary diagnostic tool for the preoperative evaluation of patients with salivary gland lesions, especially when malignancy is suspected.